SARS-CoV-2 infectivity and antigenic evasion: spotlight on isolated Omicron sub-lineages - Barrera, Aldo; Martínez-Valdebenito, Constanza; Angulo, Jenniffer; Palma, Carlos; Hormazábal, Juan; Vial, Cecilia; Aguilera, Ximena; Castillo-Torres, Pablo; Pardo-Roa, Catalina; Balcells, María Elvira; Nervi, Bruno; Corre, Nicole Le; et al. (Frontiers in Medicine, 2024)
Since the SARS-CoV-2 outbreak in 2019, a diversity of viral genomic variants has emerged and spread globally due to increased transmissibility, pathogenicity, and evasion of immunity. This fact raises the question of whether natural or vaccine-acquired immunity will be sufficient to protect the population from future waves of SARS-CoV-2. Variants of concern like Delta and Omicron have been highlighted by their predominant circulation and reduced antibody neutralization. By the first trimester of 2023 in Chile as in most countries, BQ and XBB were the predominant circulating sub-lineages of Omicron. The molecular and antigenic characteristics of variants have been mainly determined using non-authentic spike pseudoviruses, which is often described as a limitation. Also, few studies using isolates from recent Omicron sub-lineages have been conducted, indicating a need for further investigation of their characteristics and implications. In this study, we analyze the characteristics of isolated SARS-CoV-2 from clinical samples, as for the ancestral B.1.1, Delta, Omicron BA.1 and sub-lineages of BA.2 and BA.5, assessing their infectivity in cell lines and their ability to evade neutralization. On cell culture, we observed dissimilar viral plaque size, cell morphology, and cytotoxicity upon infection in Vero E6-TMPRSS2 with each variant, suggesting a decrease in the cytopathic effect compared to the ancestral B.1.1 strain. BA.2-derived sub-variants like XBB.1.5 showed attenuated viral replication, but BA.5-derived variants like BQ.1.1 resemble the replication rates of the ancestral SARS-CoV-2 virus. Similar trends were observed in intestinal Caco2 cells, except for Delta. Antibody neutralization experiments using sera from individuals infected during the first COVID-19 wave (FWI) showed a reduction in neutralization against the BA.1, as for the following Omicron sub-lineages, showing a discrete but constant decrease in neutralization. Interestingly, BQ.1.1 showed a 6.1-fold more escape to neutralization than XBB.1.5, despite being less prevalent. Neutralization patterns were similar when tested sera from individuals vaccinated with 3xBNT162b2 (PPP) or Coronavac-Coronavac-BNT162b2 (CCP) schedules; however, CCP sera showed 2.3-fold higher neutralization against XBB.1.5 than FWI and PPP. Our analysis provides important evidence regarding the balance between infectivity and antigenic escape that drives SARS-CoV-2 second-generation evolution in the population.